Konsep Dasar Pendidikan Agama Islam dan Budi Pekerti Integratif di Sekolah - Permana, Dino Yudia; Fitriani, Wahidah (Yayasan Rahmat Islamiyah, 2023)
The aim of this research is to find out the basic concepts of Islamic Religious Education and Integrative Characteristics in this school from various perspectives. This type of research is qualitative research with a literature study research method. The data collection technique in this research is by reviewing various books in the library as well as books owned by the researcher and other people as well as trusted journals. The results of this research indicate that an understanding of the basic concepts of Islamic Religious Education and Integrative Character in Schools must be understood to gain a deep understanding of it.